2021
DOI: 10.3389/fneur.2021.765203
|View full text |Cite
|
Sign up to set email alerts
|

Basal Ganglia Local Field Potentials as a Potential Biomarker for Sleep Disturbance in Parkinson's Disease

Abstract: Sleep disturbances, specifically decreases in total sleep time and sleep efficiency as well as increased sleep onset latency and wakefulness after sleep onset, are highly prevalent in patients with Parkinson's disease (PD). Impairment of sleep significantly and adversely impacts several comorbidities in this patient population, including cognition, mood, and quality of life. Sleep disturbances and other non-motor symptoms of PD have come to the fore as the effectiveness of advanced therapies such as deep brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 125 publications
0
9
0
Order By: Relevance
“…The copyright holder for this preprint (which this version posted July 5, 2022. ; https://doi.org/10.1101/2022.07.05.498300 doi: bioRxiv preprint during REM and NREM in Q84 mice is reminiscent of increased beta oscillations observed in other neurodegenerative diseases and sleep disorders. Alterations, most frequently increases, in beta oscillations have been observed during wake and sleep states in patients or animal models of PD [60][61][62][63][64][65][66][67][68] , HD 69,70,[79][80][81][82][83][84][71][72][73][74][75][76][77][78] , dementia with Lewy bodies 85,86 , insomnia 60,87 , and RBD 63,[88][89][90] . In PD, beta oscillations in the basal ganglia are usually pathological 60,62,64,67,68,91 and appear to be linked to basal ganglia dysfunction or compensation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The copyright holder for this preprint (which this version posted July 5, 2022. ; https://doi.org/10.1101/2022.07.05.498300 doi: bioRxiv preprint during REM and NREM in Q84 mice is reminiscent of increased beta oscillations observed in other neurodegenerative diseases and sleep disorders. Alterations, most frequently increases, in beta oscillations have been observed during wake and sleep states in patients or animal models of PD [60][61][62][63][64][65][66][67][68] , HD 69,70,[79][80][81][82][83][84][71][72][73][74][75][76][77][78] , dementia with Lewy bodies 85,86 , insomnia 60,87 , and RBD 63,[88][89][90] . In PD, beta oscillations in the basal ganglia are usually pathological 60,62,64,67,68,91 and appear to be linked to basal ganglia dysfunction or compensation.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations, most frequently increases, in beta oscillations have been observed during wake and sleep states in patients or animal models of PD [60][61][62][63][64][65][66][67][68] , HD 69,70,[79][80][81][82][83][84][71][72][73][74][75][76][77][78] , dementia with Lewy bodies 85,86 , insomnia 60,87 , and RBD 63,[88][89][90] . In PD, beta oscillations in the basal ganglia are usually pathological 60,62,64,67,68,91 and appear to be linked to basal ganglia dysfunction or compensation. Thus, the triad of RBD, beta oscillations, and basal ganglia appears to be a unifying feature of these diseases, including SCA3.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, it has been found that open-loop DBS improves sleep structure as a fortuitous byproduct ( Hjort et al., 2004 ; Mizrahi-Kliger et al., 2020 ). However, it is not currently optimized for nighttime or within sleep stages ( Baumgartner et al., 2021 ; Zahed et al., 2021 ). Recently, investigational trials have used newer sensing-enabled DBS devices to deliver closed loop DBS in response to biomarkers correlated with motor performance ( Gilron et al., 2021 ; Little et al., 2016 ; Velisar et al., 2019 ).…”
Section: Biological Rhythms and Neuromodulationmentioning
confidence: 99%
“…In addition to their recognized role in the development of PD motor signs 20 , our findings provide further support for the role of beta oscillations in the sleep dysfunction observed in patients with PD 11,13 . It has recently been hypothesized that parkinsonism-related excessive beta oscillations in the basal ganglia are transmitted to the cortex, disrupting the initiation or maintenance of slow wave oscillations during sleep 11,21 , though the exact mechanisms by which this occurs remain unclear. Additional investigations utilizing simultaneous recordings at the single neuron and field potential level across the basal ganglia-thalamocortical (BGTC) network will be needed to further test this hypothesis and provide key insight into the neuronal mechanisms driving the disruption of cortical delta oscillations in parkinsonian sleep and the role beta oscillations in the BGTC network may play in the emergence of sleep dysfunction in PD.…”
mentioning
confidence: 99%
“…Future preclinical studies that explore neuromodulation (e.g., both non-invasive as well as DBS 33 ) techniques for suppressing beta oscillations during sleep and characterizing its effect on cortical SWS to further support the notion that suppression of excessive beta oscillations during sleep can profoundly improve sleep quality. Moreover, simultaneous neural recordings across the basal ganglia thalamocortical network and directed connectivity analysis can help decipher the mechanisms by which beta oscillations in the cortex are elevated during SWS in the early stage of parkinsonism 11,21,34 . Lastly, a higher number of sleep recordings across normal and early PD along with machine learning algorithms will be necessary to generalize the efficacy of features discussed in this study for early-stage disease classification.…”
mentioning
confidence: 99%